ЦАХИЛДАГНЫ ТӨРЛИЙН УРГАМЛЫН ФИЛОГЕНЕТИК ХОЛБОО - Х Алтанзул; Ю Оюунбилэг (Proceedings of the Mongolian Academy of Sciences, 2016)
The phylogenetic relationship of eight Iris species (I.flavisimma, I.ventricosa, I.bungei, I.kaempferi, I.tenuifolia, I.lactea, I.tigrida, I.dichotoma) were studied by PCR using six specific primers (S-523, Z1204R, trnL, trnF and ITS1, ITS4). All species except I.ventricosa were identified when using S-523, Z1204R and trnL, trnF primers and the DNA fragment size ranged between 500 to 600 bp and 800 bp, respectively. Primers ITS1 and ITS4 produced double bands in about 500 and 1500 bp to I.bungei, I.kaempferi, and I.lactea species. On the phylogenetic tree, some iris species have close relations based on chloroplastic DNA sequences. The closest relationships showed between I.sanguinea and I.sibirica, I.rutenica and I.uniflora. Also I.tenuifolia, I.ventricosa and I.halophila located on one branch of phylogenetic tree.